Board gender diversity reform and corporate carbon emissions - Barroso, Raúl; Duan, Tinghua; Guo, Siyue (Sarina); Kowalewski, Oskar (Journal of Corporate Finance, 2024)
We examine the impact of the increased presence of female board members on corporate carbon emissions. Using the staggered enactment of gender diversity reforms in different countries, we find that an increase in the number of female directors after the reforms leads to a reduction in corporate carbon emissions. This effect is particularly more pronounced when the reform is legislative, and occurs in collectivistic countries. Furthermore, the effect of enhanced female board representation on carbon emission reduction is greater following the Paris Agreement. This study offers valuable insights for policymakers who consider gender diversity reform as a strategy against climate change.